IDENTIFIKASI TENTANG PENGGUNAAN MEDIA PEMBELAJARAN MATA PELAJARAN PRODUKTIF AKUNTANSI PADA KELAS X AKUNTANSI DI SMK NEGERI 1 SOOKO MOJOKERTO - HAMIDAH HIDAYATI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This study purpose to determine the learning media in SMK Negeri 1 Sooko Mojokerto and the reasons teachers choose the learning media, determine the feasibility of learning media. This study is a descriptive research with quantitative approach. The results showed that the learning media used in SMK Negeri 1 Sooko Mojokerto is powerpoint. From the review of learning media expert obtained the result that the learning media used in SMK Negeri 1 Sooko Mojokerto powerpoint learning media is appropriate. Keyword: learning media